The effects of in ovo injected nicotinamide riboside on avian myogenesis - Davis, Stephanie (Kansas State University, 2019)
The objective of this study was to determine the effects of in ovo injection of nicotinamide riboside (NR) on avian embryonic myogenesis. In experiment one, fertilized broiler eggs (n=156; Cobb 500) were randomly assigned to 1 of 4 treatments in a completely randomized design with a 2 × 2 factorial arrangement. Factor 1 consisted of treatment (TRT), with eggs injected with 100 μl of 0.0 (-) or 2.5 mM (+) NR in sterile saline. Factor 2 was injection location (LOC), with either treatment injected into the yolk (YO) or albumin (AL). Post-hatch, chicks were euthanized and body and pectoralis major (PM) measures were examined. The left PM was kept for muscle fiber analysis. There were no TRT×LOC interactions for all body and PM measures (P ≥ 0.07), except PM weight and length (P < 0.01). Pectoralis major muscles from the YO+ treatment were heavier (P < 0.01) than all other treatments. Length of PM from AL+ were longer than control chicks injected into either the yolk or albumen (P < 0.04), but was shorter (P < 0.01) than YO+ chicks. There was a TRT×LOC interaction for muscle fibers per 1000μm² with YO+ muscles having the largest number of fibers (P < 0.01) compared to all other treatments, which did not differ (P ≥ 0.16) from each other. There were no TRT×LOC (P ≥ 0.43) interactions for muscle fiber cross sectional area. Injected NR increased PM muscle development and greater effects were seen when NR is injected into the yolk. In experiment two, the effect of increasing in ovo NR concentration on avian myogenesis was examined. Fertilized broiler eggs (n=420; Cobb 500) were randomly assigned to 1 of 4 treatments: 0.0, 2.5, 5.0, or 10.0 mM NR made in 0.9% sterile saline. At d10 of incubation, 100μl of allotted treatment was injected only into the egg yolk. After euthanasia, body measures, PM measures, leg area, and muscle fiber characteristics were analyzed for broiler chicks. For d21 chicks, there were no treatment differences for body measures (P≥0.08), excluding head length and chest width, which were larger (P≥0.05) from 2.5mM NR compared to the saline treatment. The weight and width of chick PM were increased (P<0.01) at every NR level. Chicks given 2.5 and 5mM NR solutions had longer PM measurements (P≤0.01) than saline chicks. Injection of 5mM NR increased PM depth (P≤0.04) from d21 chicks. Treatment did not affect leg muscle area or muscle fiber CSA (P≥0.20). All NR injections increased muscle fiber number (P<0.01); though 10mM injection led to the largest increase in fibers (P<0.01). Injecting up to 5.0 mM NR in the yolk of the developing embryo did not affect body weight but increased PM measures, indicating NR influenced avian myogenesis.
Keywords: Broiler; In ovo injection; Nicotinamide riboside; Muscle fiber; Pectoralis major